Women and Fashion at the end of Nineteenth Century: Marketing Strategies for Fashion Consumption to Encourage the Development of Capitalism in Spain - Bello-Bravo, Julia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2015)
At the end of the nineteenth century and at the beginning of the twenty-century, the media was the best marketing tool to acknowledge the importance of fashion for women. Some magazines targeted adult female audiences to inform them about fashion with the ultimate goal of encouraging women’s participation and consumption. A good example appeared in the magazine “La Mujer” where parallel and contradictories discourses existed regarding the effects that fashion produces in women and society. The media expressed the importance of fashion for women especially beauty but at the same time it justified that women’s beauty should be pursued only to please the husband in the case of married women or to find a husband in the case of single women. The media used marketing strategies such as visual images, fashion designs, pictures, etc., to construct a new female model more in keeping with modernity. Fashion publicity in the media allowed women to acquire a sense of participation in the context of modernity and urban settings where the consumption of fashion took place. Additionally, fashion facilitated the capitalist development of the country.